Predictive Factors in Malignant Melanoma - Noveski, Lazo; Dzokik, G; Pejkova, S; Dzonov, B; Peneva, M (Macedonian Association of Anatomists and Morphologists, 2012)
The vertical melanoma thickness according to Breslow, the anatomical level of the tumor skin invasion according to Clark, mitotic activity in the tumor cells, the type and the phase of growth of the tumor, the localization, the local inflammatory response to the tumor cells and the presence of the tumor infiltrating lymfocytes as well as the age and the sex of the patient are considered as factors which could influence the prognosis of the melanoma. The aim of this study was to define the correlation between the predicting factors of malignant melanoma (vertical melanoma thickness according to Breslow, the presence of the ulceration and the presence of tumor infiltrating lymphocytes), and the presence of metastasis in the sentinel lymph nodes, and, to determine the predicting value of these factors in patients with malignant melanoma of the skin. Thirty patients with malignant melanoma who had undergone surgery at the University Clinic for Plastic and Reconstructive Surgery in Skopje in the period from 2005 until 2009, were retrospectively evaluated. The following parameters were analyzed: primary tumor thickness according to Breslow, presence of ulcerations, lymphocytic infiltration and their relation with onset of metastases in the sentinel lymph node. The results showed that there was a statistically significant correlation of the vertical thickness of the tumor according to Breslow and the presence of the lymphocytic infiltration with the sentinel node positivity for metastasis. Higher value of Breslow indicates higher possibility for metastasis in the sentinel nodes. A more intense tumor lymphocytic infiltration is related to the lower possibility for metastasis in the sentinel nodes. The correlation between the ulceration of the melanoma lesion and the positivity for metastasis of the sentinel node was statistically insignificant.
Keywords: malignant melanoma; lymph node; metastasis